RANCANG BANGUN APLIKASI RESEP KULINER BERBASIS ANDROID MENGGUNAKAN KODULAR: DESIGN AND BUILD APPLICATION OF CULINARY RECIPES BASED ON ANDROID USING KODULAR - Fitri Eka Budi Suciati; Julius Panda Putra Naibaho; Lion Ferdinand Marini (JISTECH: Journal of Information Science and Technology, 2022)
Indonesian food is one form of culinary that reflects the diversity of cultures that exist in Indonesia (Dewi, 2020). Culinary results from processed dishes such as side dishes, food and drinks. Culinary is inseparable from cooking activities related to food, starting from the preparation of tools and materials, how to cook, serve and enjoy the results of the dishes. Currently, there are a lot of information media about recipes ranging from recipe books, magazines, internet and so on. However, every recipe in it uses measured ingredients such as measuring cups, measuring spoons and scales. those of us who do not have these tools will estimate carelessly so as to produce less than optimal dishes. Based on these problems, a culinary recipe application was made. The method used for research is the waterfall method, where each stage is done first before moving on to the next stage. With the results of the study using application testing, namely Black Box testing and user surveys in the form of questionnaires. The results of the application test show that the application can run well and the results of the user survey show that the highest number of respondents scores in agree with a total of 60 points and strongly agrees with 30 points, while the lowest agrees with 9 points and disagrees with 1 point. The final result in the research that the author has done is that the culinary recipe application can help users find recipes and get to know and be able to cook dishes using existing tools and materials, with this application users do not need to come to the store to buy recipe books.